2014
DOI: 10.1371/journal.pone.0086049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and DNA Methylation Changes in Cotton (Gossypium) Genotypes and Tissues

Abstract: In plants, epigenetic regulation is important in normal development and in modulating some agronomic traits. The potential contribution of DNA methylation mediated gene regulation to phenotypic diversity and development in cotton was investigated between cotton genotypes and various tissues. DNA methylation diversity, genetic diversity, and changes in methylation context were investigated using methylation-sensitive amplified polymorphism (MSAP) assays including a methylation insensitive enzyme (BsiSI), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 84 publications
4
42
1
Order By: Relevance
“…More recently, Whole Genome Bisulfite Sequencing in three Brassicaceae species found lower methylation levels in roots than shoots, with changes between the two tissues being more frequent at repetitive sites and transposons, although across-species variation in cytosine methylation patterns was larger [3]. Here, we found that, in E. cicutarium, methylation was also lower in roots than in above ground leaves (see [47,50] for similar results in chicory and cotton, respectively). Scarcity of studies, disparity of the analytical methods that were used to quantify cytosine methylation, and some contrasting results between the few species analyzed in more detail (see e.g., [51]) precludes us to ascertain whether, apart from a reduced methylation level in endosperm, methylation varies among plant tissues in some definite way [52].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…More recently, Whole Genome Bisulfite Sequencing in three Brassicaceae species found lower methylation levels in roots than shoots, with changes between the two tissues being more frequent at repetitive sites and transposons, although across-species variation in cytosine methylation patterns was larger [3]. Here, we found that, in E. cicutarium, methylation was also lower in roots than in above ground leaves (see [47,50] for similar results in chicory and cotton, respectively). Scarcity of studies, disparity of the analytical methods that were used to quantify cytosine methylation, and some contrasting results between the few species analyzed in more detail (see e.g., [51]) precludes us to ascertain whether, apart from a reduced methylation level in endosperm, methylation varies among plant tissues in some definite way [52].…”
Section: Discussionsupporting
confidence: 75%
“…Scarcity of studies, disparity of the analytical methods that were used to quantify cytosine methylation, and some contrasting results between the few species analyzed in more detail (see e.g., [51]) precludes us to ascertain whether, apart from a reduced methylation level in endosperm, methylation varies among plant tissues in some definite way [52]. The high-performance liquid chromatography (HPLC) method applied here could help to provide precise and genome reference-free global measure of DNA cytosine methylation, useful as a molecular phenotype for tissue-specific comparisons among and within species (see e.g., [47,50]) that could improve our current understanding of epigenetic regulation during plant development in a broader range of plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Including a third schizomer ( Bsi SI) with the same cleavage site but insensible to any methylation and/or the addition of the combined digestion of the two isoschizomers ( Hpa II + Msp I) may help to reduce uncertainty of some ambiguous results and improve reliability of MSAP interpretations if subsequent increased costs are affordable (Fulneček & Kovařík ; Osabe et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…2008; Vanyushin and Ashapkin 2011; Osabe et al. 2014). Irrespective of mechanisms, our results emphasize the importance of adopting scoring approaches in future MSAP‐based ecological epigenetics studies that allow to differentiate spatial structure, variability levels, transgenerational constancy and phenotypic correlates of cytosine methylation marks in different genomic contexts.…”
Section: Discussionmentioning
confidence: 99%